Gestão Inteligente de Estacionamento em Ambiente Urbano - Oliveira, Filipe (2019)
The use of new technologies in service modernization and resource management, aiming at developing more sustainable cities and improving the quality of life of citizens, is at the base of Smart Cities and Internet of Things paradigms. In this context, technologies such as wireless sensor networks assume a preponderant role. This paper targets a specific problem of Smart Cities, proposing a smart parking system for urban environments, which intends to increase the efficiency in managing parking while improving drivers experience in finding an available place. Taking into account user profiles and the existence of indoor/outdoor parks, this article presents a model of intelligent parking, its main components and attributes taking the city of Braga as case study. As proof of concept, a simulation prototype was developed using CupCarbon, for defining and testing the proposed parking management scenarios.